Perception and Control Module of the Automatic Tracking System forAutonomous-rail Rapid Tram - YUAN Xiwen; FENG Jianghua; HU Yunqing; ZHANG Xinrui; HUANG Ruipeng; LIN Jun; YUAN Hao (Kongzhi Yu Xinxi Jishu)
The automatic tracking system enables the transit front axle to automatically follow the digital virtual central line. Under the condition of incomplete road information and random vehicle vibration, its perception subsystem that builds a stable virtual track via image recognition solves the problem of information separation, identification, feature extraction and continuous digital virtual central line generation. Its control subsystem achieves automatic and accurate first axle entry and tracking of digital virtual center line, while normally the transit architecture is special and under random initial attitude. The principle and scheme of automatic tracking system were presented, and the digital virtual central line recognition algorithm based on deep learning was also introduced. Considering that autonomous-rail rapid transit is a complicated nonlinear with large time delay system, two automatic tracking control methods of PID and MPC considering time delay were derived in detail. Finally, the effectiveness of the algorithm was verified by both co-simulation and the real vehicle test. The results show that the precise docking clearance between the platform and the first carriage is kept at about 10 cm. When driving at high speed, the lateral deviation is controlled within ± 15 cm, achieving the industry leading level.